'The tactics of disruption', TUC, 1949 (1949)
1949 1945-1960 "'The tactics of disruption', TUC, 1949" [T0348.jpg], 1949, Trades Union Congress This pamphlet issued by the TUC in 1949 expressed concern over the influence of the Communist Party within trade unions and trades councils.